Effect of Crude Extracts Fern Leaves as Biostimulants on Biomass and Nodulation of Soybean (Glycine max L.) - Dilla, Arfa Iskhia; Noli, Zozy Aneloi; Mansyurdin, Mansyurdin (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Soybean (Glycine max) is a primary food commodity for the people in Indonesia, with most of its needs still dependent on imports. Efforts to increase local production require a sustainable strategy, including by use biostimulants. Natural biostimulants, such as fern leaf extract, is proven to be a solution in increasing the growth of plants. This study aims to evaluate the potential use of fern leaf extract as a biostimulant on biomass and the number of root nodules in soybean plants. The method used in this study was a factorial complete randomized design with 2 factors and 3 replications. Factor A is the source of crude extract of fern leaves, control, Gleichenia linearis, Diplazium esculentum, Nephrolepis exaltata, and Blechnum orientale. Factor B is the frequency of application extracts, namely 1 time and 2 times.The results showed that the application of Diplazium esculentum leaf extract with one application significantly increased the total number of root nodules, the number of effective root nodules and vegetative phase biomass. While in Nephrolepis exaltata with one time application can significantly increase the number of total root nodules and the number of effective root nodules. This increase is indicated by the content of bioactive compounds contained in the extract, so that it can increase the growth of soybean plants by stimulating the activity of soil microorganisms.